A new species of Pangrapta Hübner, 1818 from China (Lepidoptera, Erebidae, Pangraptinae) - Hu, Yan-Qing; Yu, Yong; Wang, Min (Zootaxa, 2017)
Pangrapta is a large and morphologically rather diverse genus, which is widely distributed in the New and the Old Worlds. This genus usually has a dark brown ground color on wing and wing margin is often slightly angled; a majority of species have the triangle patch on the forewing costa between subterminal and postmedial lines; uncus is generally slender and tapering apex; valva tends to be long and narrow; harpe is often spine-shaped; vesica typically has one or more cornuti on the diverticula. As currently, Pangrapta is consisted of about 100 species in the world (Hu & Wang, 2013), which is called for a general revision.